ECTHR_COMMITTEE 38985/21 vom 14. Oktober 2025 , AFFAIRE MEDAROV c. BULGARIE - Ecthr Committee (2025)
Violation de l'article 6 - Droit à un procès équitable (Article 6-2 - Présomption d'innocence); Violation: 6;6-2